HUBUNGAN AKTIVITAS FISIK DAN STRES DENGAN KEJADIAN HIPERTENSI PADA PRA-LANSIA DI RSUD DR. R. SOEDJONO SELONG - LOMBOK TIMUR - Dinda Furqonnisa Maligan; Mamang Bagiansah; Siti Ruqayyah; Rusmiatik (Nusantara Hasana Journal, 2023)
Hypertension is an increase in systolic blood pressure >140 mmHg and diastolic blood pressure >90 mmHg, also known as the silent killer. Risk factors for hypertension are categorized into modifiable risk factors i.e. physical activity and stress, and non-modifiable risk factor i.e. age. As a person becomes older, the elasticity of blood vessels will decrease, thereby increasing the prevalence of hypertension at the age of 45 years and beyond. Objective to find out the association of physical activity and stress with hypertension incidence among pre-elderly in RSUD DR. R. Soedjono Selong, East Lombok. This study was an observational analytic quantitative study with a cross-sectional design. The sampling technique used was simple random sampling. This study was conducted in RSUD DR. R. Soedjono Selong, East Lombok in November-December 2022. The sample was 30 respondents. The data obtained were analyzed by Chi Square test with a significance value (p ≤ 0.05). 73% of the 30 sample respondents were hypertension patients who had moderate physical activity, 10% had mild, and none had heavy physical activity. For stress category 60% was moderate, 13% light, and 10% severe. 7% of the 30 sample respondents did not suffer from hypertension and had moderate physical activity, 3% had light and 7% had heavy. For stress category none was moderate, 13% mild and 10% severe. A value of p = 0.018 (p <0.05) was obtained for the association of physical activity with hypertension incidence among pre-elderly, and a value of p = 0.001 (p <0.05) was obtained for the association of stress with hypertension incidence among pre-elderly. There was a significant association of physical activity and stress with hypertension incidence among pre-elderly in RSUD DR. R. Soedjono Selong, East Lombok.